A new microfluidic methodology to assess the haemocompatibility of magnetic nanoparticles designed for theranostic applications - Rodrigues, Raquel Oliveira (2016)
The remarkable physicochemical properties of magnetic nanoparticles (MNPs) at the nanoscale have boosted the development of new and promising strategies for the simultaneous diagnosis and treatment of diseases, particularly in cancer therapy Ð the so-called theranostic applications (1). In these strategies, the intrinsic superparamagnetic properties of MNPs have been exploited to gain access into multifunctional systems able to simultaneously perform as enhanced magnetic resonance imaging (MRI) contrast agents, efficient nanocarriers for drug delivery and nanoheaters in magnetic hyperthermia based therapy (2), among others.